2008
DOI: 10.1353/csd.2008.0002
|View full text |Cite
|
Sign up to set email alerts
|

"It Takes a Village to Raise a Child": The Role of Social Capital in Promoting Academic Success for African American Men at a Black College

Abstract: Historically Black colleges and universities (HBCUs) were created to provide educational opportunities for African Americans when other higher education venues restricted their participation. HBCUs are credited with nurturing and producing leaders who embraced W. E. B. Du Bois's concept of the "Talented Tenth," and exhibiting fortitude in advancing social equality for all. Over the years, as legalized segregation was overturned and efforts were made to expand opportunities for African Americans, some have ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(169 citation statements)
references
References 49 publications
8
161
0
Order By: Relevance
“…The first year of college can be challenging, particularly for those students who are the first in their families to attend college and/or are from underserved groups (Owens, Lacey, Rawls, & Holbert-Quince, 2010;Phinney, Campos, Cidhinnia, Padilla Kallemeyn, & Kim, 2011). Mentoring has the potential to support national and institutional goals to increase the number of persons completing college degrees by providing access to social capitalopportunities and resources provided through relationships and interpersonal networks (Palmer & Gasman, 2008)-and cultural capital, or social assets that promote mobility (Cole & Espinoza, 2008). Through mentoring programs, students participate in activities aimed at development in areas such as study skills, time management, and written and oral communication skills (Michael, Dickson, Ryan, & Koefer, 2010;Salinitri, 2005), providing opportunities to identify ways of successfully navigating the college environment.…”
Section: Importance and Value Of Mentoringmentioning
confidence: 99%
“…The first year of college can be challenging, particularly for those students who are the first in their families to attend college and/or are from underserved groups (Owens, Lacey, Rawls, & Holbert-Quince, 2010;Phinney, Campos, Cidhinnia, Padilla Kallemeyn, & Kim, 2011). Mentoring has the potential to support national and institutional goals to increase the number of persons completing college degrees by providing access to social capitalopportunities and resources provided through relationships and interpersonal networks (Palmer & Gasman, 2008)-and cultural capital, or social assets that promote mobility (Cole & Espinoza, 2008). Through mentoring programs, students participate in activities aimed at development in areas such as study skills, time management, and written and oral communication skills (Michael, Dickson, Ryan, & Koefer, 2010;Salinitri, 2005), providing opportunities to identify ways of successfully navigating the college environment.…”
Section: Importance and Value Of Mentoringmentioning
confidence: 99%
“…Researchers indicate that MSIs historically enroll, retain, and graduate a larger number of students of color due to an increased focus on the cultural background of those students [18,26,27]. Unlike the experience for students of color in non-MSIs, MSIs are more likely to better cater to those students with more limited academic preparation.…”
Section: Culturally Relevant Pedagogymentioning
confidence: 99%
“…The majority of these studies is qualitative and explores the benefits to students of culturally driven pedagogies, support services, and course work [26,27,30,33,34]. Culturally relevant pedagogies emphasize the cultural empowerment of a student's background and community.…”
Section: Culturally Relevant Pedagogymentioning
confidence: 99%
“…Steel also finds that Black students' success was increased if Black faculty was present to serve as role models. Palmer & Gasman (2008) found that having professors of the same race increased self-efficacy and confidence.…”
Section: Cultural Competency Weiner (1999) Research On the Reflectiomentioning
confidence: 99%
“…Ladson Billings (1995) defines culturally relevant pedagogy as, "pedagogy that empowers students intellectually, socially, emotionally, and politically by using cultural referents to impart knowledge, skills, and attitudes" (Howard, 2001, p. 181) . Holistic education is a pedagogy that engages students in their development both academically and personally (Palmer & Gasman, 2008) . Overall do science professors at your institutions practice cultural relevant pedagogy and holistic education?…”
Section: Confidentiality Of Recordsmentioning
confidence: 99%